Driving cessation among older adults in a Caribbean small island developing state. (September 2020) - Brown, Catherine R.; Howitt, Christina; Murphy, Madhuvanti M.; Hambleton, Ian R.; Crizzle, Alex M.
Abstract: Objective: Driving cessation is associated with adverse psychosocial and health consequences, and adaptation to life without driving can be challenging. This study sought to explore the experiences of older adults living in Barbados, a Small Island Developing State (SIDS) who have ceased driving; their use of alternate transportation; and how well their neighbourhoods support a physically and socially active lifestyle. Methods: In-depth semi-structured interviews were conducted with seventeen older adults. Interviews were transcribed verbatim and analysed using thematic analysis and the constructionism lens theory. Results: Driving cessation was not a major concern for participants. Social support from friends and family contributed greatly to this ease of transition, along with relief and enjoyment of being a passenger (rather than driver) and the enjoyment of hobbies. Rides from friends and family served as the major mode of transportation, while public transportation and taxis were met with negativity and disinterest. Neighbourhoods played an important role in this transition as they represented a significant source of social capital and close proximity to facilities and stores. Conclusion: Social and geographical idiosyncrasies of being a SIDS may contribute to the more positive experience of driving cessation of this study as compared to larger, more industrialized countries. Efforts to improve the physical and social health of older adults in Barbados should focus on external factors that encourage walking and further social engagement, such as improving neighbourhood infrastructure, improving the acceptability of public transportation, and increasing the range of alternative transportation options. Highlights: Older adults contented in stopping driving in this small island developing state. Unique social and geographical features contribute to positive experiences. Efforts to support non-drivers should encourage walking and social engagement. Alternative transportation options should be better suited to older adults.